Database tuning : principles, experiments, and troubleshooting techniques - Shasha, Dennis Elliott (Morgan Kaufmann series in data management systems., 2003)
Tuning your database for optimal performance means more than following a few short steps in a vendor-specific guide. For maximum improvement, you need a broad and deep knowledge of basic tuning principles, the ability to gather data in a systematic way, and the skill to make your system run faster. This is an art as well as a science, and Database Tuning: Principles, Experiments, and Troubleshooting Techniques will help you develop portable skills that will allow you to tune a wide variety of database systems on a multitude of hardware and operating systems. Further, these skills, combined with the scripts provided for validating results, are exactly what you need to evaluate competing database products and to choose the right one. * Forward by Jim Gray, with invited chapters by Joe Celko and Alberto Lerner * Includes industrial contributions by Bill McKenna (RedBrick/Informix), Hany Saleeb (Oracle), Tim Shetler (TimesTen), Judy Smith (Deutsche Bank), and Ron Yorita (IBM) * Covers the entire system environment: hardware, operating system, transactions, indexes, queries, table design, and application analysis * Contains experiments (scripts available on the author's site) to help you verify a system's effectiveness in your own environment * Presents special topics, including data warehousing, Web support, main memory databases, specialized databases, and financial time series * Describes performance-monitoring techniques that will help you recognize and troubleshoot problems.